2020
DOI: 10.1371/journal.pone.0229416
|View full text |Cite
|
Sign up to set email alerts
|

Using comparative genomics to understand molecular features of carbapenem-resistant Acinetobacter baumannii from South Korea causing invasive infections and their clinical implications

Abstract: Acinetobacter baumannii is a highly potent nosocomial pathogen that is associated with increased in-hospital mortality. Here, we investigated the changes in molecular characteristics of carbapenem-resistant A. baumannii (CRAB) isolated from the blood samples of patients admitted to a tertiary hospital in South Korea from January 2009 to July 2015. Whole genome sequencing using the Illumina MiSeq platform and multi-locus sequence typing (MLST) were performed for 98 CRAB clinical isolates. In silico analyses for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Carbapenem-resistant A. baumannii ST195 and ST208 are widespread in the world, and are dominant mainly in the Far East, e.g., in China [ 36 , 37 , 38 , 39 , 40 ]. Furthermore, the ST208/ST1806 strains have been isolated in South Korea [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenem-resistant A. baumannii ST195 and ST208 are widespread in the world, and are dominant mainly in the Far East, e.g., in China [ 36 , 37 , 38 , 39 , 40 ]. Furthermore, the ST208/ST1806 strains have been isolated in South Korea [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the molecular epidemiology of A. baumannii , focusing on its carbapenem resistance and virulence [ 6 8 ]. Few studies pay attention to the whole genome characteristics of clinical isolates from diverse infection sites.…”
Section: Introductionmentioning
confidence: 99%
“…AMR prediction with ResFinder and KmerResistance showed high concordance, with most of the resistance genes identified commonly. The isolates showed a common antibiotic resistance profile reported in multidrug-resistant A. baumannii in Korea [ 32 , 42 , 43 ]. A previous study showed high concordance with ResFinder, an assembly-based tool, and KmerResistance, a read-based tool, in high-quality sequencing results, as in our study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%